Intermittent hypoxia is a proinflammatory stimulus resulting in IL‐6 expression and M1 macrophage polarization. Issue 4 (18th May 2017) - Schaefer, Esperance; Wu, Winona; Mark, Christina; Yang, Andrew; DiGiacomo, Erik; Carlton‐Smith, Charles; Salloum, Shadi; Brisac, Cynthia; Lin, Wenyu; Corey, Kathleen E.; Chung, Raymond T.
Abstract : The biological factors that promote inflammation or nonalcoholic steatohepatitis (NASH) in the setting of nonalcoholic fatty liver disease remain incompletely understood. Clinical studies have demonstrated an association between obstructive sleep apnea (OSA) and both inflammation and fibrosis in NASH, but the mechanism has not been identified. In this study, we use in vitro modeling to examine the impact of intermittent hypoxia on the liver. Hepatocyte, stellate cell, and macrophage cell lines were exposed to intermittent or sustained hypoxia. Candidate genes associated with inflammation, fibrosis, and lipogenesis were analyzed. Circulating cytokines were assessed in human serum of patients with nonalcoholic fatty liver disease. Intermittent hypoxia results in significant induction of interleukin (IL)‐6 expression in both hepatocytes and macrophages. The increase in IL‐6 expression was independent of hypoxia inducible factor 1 induction but appeared to be in part related to antioxidant response element and nuclear factor kappa B activation. Mature microRNA 365 (miR‐365) has been demonstrated to regulate IL‐6 expression, and we found that miR‐365 expression was decreased in the setting of intermittent hypoxia. Furthermore, macrophage cell lines showed polarization to an M1 but not M2 phenotype. Finally, we found a trend toward higher circulating levels of IL‐6 in patients with OSA and NASH. Conclusion : Intermittent hypoxia acts as a potent proinflammatory stimulus, resulting in IL‐6 induction and M1 macrophage polarization. Increased IL‐6 expression may be due to both induction of antioxidant response element and nuclear factor kappa B as well as inhibition of miR‐365 expression. Higher levels of IL‐6 were observed in human samples of patients with OSA and NASH. These findings provide biological insight into mechanisms by which obstructive sleep apnea potentiates inflammation and fibrosis in patients with fatty liver disease. ( Hepatology Communications 2017;1:326–337)